The Public’s Perception of the Government Employees’ Services at Fandoi District, Biak Numfor Regency, Papua Province. - Sudarman, Fatmawada; Laha, M. Saleh (GNOSI: An Interdisciplinary Journal of Human Theory and Praxis, 2020)
To deliver high-quality services by the government to the public is one of many problems that often create various perceptions from the community. The low quality of services delivered by government employees is one problem that should be overcome by the government. This study aims to analyze the public's perceptions of government employees’ services at Fandoi district, Biak Numfor Regency, Papua province. The method used is descriptive research by describing the phenomena and data obtained in the field with a percentage using a frequency table. The results showed that the public's perception of the government employee services in Fandoi district, Biak Numfor Regency, Papua Province, was in quite a good category, with a summary of respondents' answers on 70.93%, which was in the interval of 56% -75%. However, there is still a gap between the public perceptions and the services provided by government employees where there are still shortages and constraints in services. Therefore, various policies to improve the service quality need to be taken by the government.